Reflection of Gus Dur Thoughts and Movements in The View of Cirebon Figures - Muhammad Maskur Musa; Muhammad Minanur Rahman; Rizki Fauzi (Al Qalam, 2023)
The influence of one’s leadership is influenced by charisma and a lifelong struggle to be a leader. Leaders who have a good profile will always be an encouragement and inspiration for change, even after the leader has long died. To achieve this, a leader must be able to realize the vision in the reality of life. The purpose of this study is to explain the reflection of Gus Dur’s thoughts and movements in the view of Cirebon figures. The method used in this research is library research with a descriptive qualitative approach. A literature review of various relevant sources, such as books, journals, and other scientific articles, is used to collect data. The results showed that K.H. Abdurrahman Wahid, commonly known as Gus Dur, produced many ideas and thoughts with the movements he made. These ideas and thoughts are not only for the benefit of a group; they are for the benefit of humanity, especially the Indonesian nation. Many of Gus Dur’s ideas and thoughts, especially regarding humanity, were produced, including the indigenous Islam, pluralism, and defending minorities. Some of the ideas and thoughts produced by Gus Dur were reflected in a movement. As a result, the Indonesian people, including Cirebon figures, can continue to reflect their ideas and thoughts in the form of movements in their daily lives.